1971
DOI: 10.3758/bf03332483
|View full text |Cite
|
Sign up to set email alerts
|

The pigeon’s concept of pigeon

Abstract: Pigeons were trained to discriminate between the presence and absence oe a pigeon in photographie displays projected on a response key. Irrelevant cues were reduced as much as possible, while the differences between the objects were of sufficient variety and complexity to ensure that mastery of the discrimination would require the use of a concept. The Ss learned this discrimination very rapidly. On a test given following training, the Ss showed almost complete transfer to new displays containing fancy breeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 2 publications
1
27
1
Order By: Relevance
“…dominants and subordinates). Thus, pigeons trained to discriminate between pictures of a variety of animals detect pigeon-like stimuli and seem to form an abstract representation, or concept, of several animal species including their own (Poole and Lander, 1971;Herrnstein et al, 1976;Watanabe, 1992). In these tests as in others, carried out also with domestic chickens, the images of conspecifics and of nonconspecifics were those of socially unfamiliar individuals (Ryan and Lea, 1994).…”
Section: Social Categories: Recognition Of Conspecifics and Identificmentioning
confidence: 99%
“…dominants and subordinates). Thus, pigeons trained to discriminate between pictures of a variety of animals detect pigeon-like stimuli and seem to form an abstract representation, or concept, of several animal species including their own (Poole and Lander, 1971;Herrnstein et al, 1976;Watanabe, 1992). In these tests as in others, carried out also with domestic chickens, the images of conspecifics and of nonconspecifics were those of socially unfamiliar individuals (Ryan and Lea, 1994).…”
Section: Social Categories: Recognition Of Conspecifics and Identificmentioning
confidence: 99%
“…After learning the discrimination between the two categories (e.g., male and female faces), pigeons are then tested with novel stimuli from each category to assess whether the discrimination is restricted to the training photographs. Accurate performance with novel stimuli traditionally has been considered as evidence that performances in training are not due simply to memorizing which stimuli are S and which are S but, instead, reflect a true categorical discrimination (e.g., Herrnstein & Loveland, 1964;Herrnstein et al, 1976;Poole & Lander, 1971;Roberts & Mazmanian, 1988;Watanabe, Sakamoto, & Wakita, 1995).…”
mentioning
confidence: 99%
“…Poole and Lander (1971) demonstrated that pigeons could learn to discriminate between pictures of different breeds of pigeons, other animals, and nonliving objects. Malott and Siddall (1972) used pictures of people, and Cerelia (1979) reported that pigeons could learn to discriminate between oak leaves and could respond to 40 new stimuli without a discrimination decrement.…”
Section: Discussionmentioning
confidence: 99%